2021
DOI: 10.1038/s41598-021-95071-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genes involved in biosynthesis of dihydroquercetin and dihydromyricetin in Ampelopsis grossedentata

Abstract: Dihydroquercetin (DHQ), an extremely low content compound (less than 3%) in plants, is an important component of dietary supplements and used as functional food for its antioxidant activity. Moreover, as downstream metabolites of DHQ, an extremely high content of dihydromyricetin (DHM) is up to 38.5% in Ampelopsis grossedentata. However, the mechanisms involved in the biosynthesis and regulation from DHQ to DHM in A. grossedentata remain unclear. In this study, a comparative transcriptome analysis of A. grosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…However, the highest content detected in this study was only about 23% of the dry weight. This might be because DHM was different in different strains [ 22 ] and growth environments. Interestingly, the tendrils also contained a high DHM content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the highest content detected in this study was only about 23% of the dry weight. This might be because DHM was different in different strains [ 22 ] and growth environments. Interestingly, the tendrils also contained a high DHM content.…”
Section: Discussionmentioning
confidence: 99%
“…Without considering the correctness of sequence length, they annotated 18 for Ag F3H, 8 for Ag F3′5′H, and 1 for Ag F3′H. Yu et al [ 22 ] elucidated candidate genes involved in the biosynthesis and regulation of flavonoids (DHM and DHQ) through comparative transcriptome analysis. In their study, they found that the upregulation of Ag F3′5′H expression increased the DHQ and DHM contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthesis pathway of flavonoids is dependent on F3H , F3′H , and F3′5′H . They catalyse the hydroxylation of flavonoids required for anthocyanin production, such as dihydrokaempferol, dihydromyricetin, and dihydroquercetin [ 42 , 43 ]. F3H catalyses the conversion of naringenin to dihydroflavones.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroquercetin (DHQ) is a pharmacologically active, which can be converted to dihydromyricetin (DHM). Yu Z. et al (2021) used HPLC to detect the DHM content in Ampelopsis grossedentata from different geographical locations and divided into two groups: B group (low DHM) and D group (high DHM). Then, Illumina HiSeq 2000 sequencing platform was performed to sequence the transcriptome of A. grossedentata from B and D groups and annotated 57,016 unigenes in D group using seven public protein databases.…”
Section: Pharmacodynamic Genes Mining For the Chronic Complex Diseasesmentioning
confidence: 99%